Pengenalan Manajemen Referensi (Mendeley) Guna Meningkatkan Wawasan Mahasiswa Pra Skripsi Fakultas Ekonomi Universitas Muhammadiyah Buton - Nining Asniar Ridzal; Ernawati Malik; Waode Adriani Hasan; I Wayan Sujana; Dewi Mahmuda (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2022)
Each university has a goal to improve the quality of human resources and has a good reputation in the surrounding environment. To achieve this, universities need to make a breakthrough. One of them is improving the quality of scientific work by students. For this reason, this activity aims to provide knowledge, understanding, and insight to students of the Faculty of Economics, University of Muhammadiyah Buton about reference management using Mendeley software. This application has a function as a citation tool and bibliography generator. Using this application will make it easier for students when compiling a final project (thesis) by paying attention to the ethics of writing scientific papers so that they can improve the quality of writing Thesis or Scientific Work. The method used in the implementation of this activity is the method of lecture, discussion and practice. The result of this activity is an increase in understanding of Mendeley reference management and an increase in the skills of pre-thesis students in operating the Mendeley application. The success is shown by the activities that run smoothly, the enthusiasm of the participants is quite high, the students have been able to write references and make a bibliography.